Sufism-Based Psychotherapy Strategies in Preventing Toxic Relationships Among Gen Z Students at Pond - Umi Ni’matin Choiriyah; Farhan Firdian (Jurnal Spiritual Healing, 2026)
This writing discusses the application of Sufistic values to prevent toxic relationship problems among Gen Z at the KH. Sholeh Darat Islamic Boarding School, PCNU, Semarang City. The study focuses on the tasawuf (Sufism) values implemented for the students (santri) to prevent toxic relationships. The dissemination of Sufi teachings is conducted by integrating scholarly knowledge with spiritual practice. In addition to exploring the intellectual heritage of scholars through the study of classical Islamic texts (kitab kuning), congregants are encouraged to cultivate spiritual purity through the tradition of collective prayer (istighosah. The research employed a qualitative method, focusing on the study of student peer relationships, with both female and male students, within the Pesantren and school setting. Data was collected through in-depth interviews, documentation, and observation. The research results indicate that students who apply Sufistic values in their daily lives can prevent themselves from toxic relationships, both in friendships and romantic relationships among Gen Z students.